Gumboots, Bhaca migrants, and Fred Astaire: South African worker dance and musical style - Muller, Carol; Topp Fargion, Janet (International Library of African Music, 1999)
On Saturday 6 January 1996, gumboot dance team leader Blanket Mkhize threw a party and slaughtered a sheep at his homestead in the southern part of KwaZulu Natal. He had informed his local chief that he and his neighbours would be welcoming to his homestead ourselves, the two white women that he had taught to gumboot dance in Durban in 1985. As with all traditional Zulu celebrations, an animal was slaughtered and its meat shared with the community and guests, utshwala (traditional sorghum beer) was brewed beforehand and competitive song and dance took place. Blanket's own sons and their friends who lived in Jolivet (near Ixopo) had been rehearsing their gumboot dance team, and a second team arrived in a mini-bus taxi from Creighton, the Bhaca1 2 area in southern KwaZulu Natal. Most of the members of the second team were migrant workers employed by the parastatal company Spoomet that was formerly the state-controlled South African Railways.
Keywords: South Africa; African Music